Xestioplexia gen. n. with the description of a new species from China (Lepidoptera: Noctuidae) - Gyulai, Peter; Ronkay, László; Saldaitis, Aidas (Zootaxa, 2015)
The taxonomic interpretation of the phyletic lineages of the Xestia s.l. generic complex is an evergreen problem of the noctuid workers. This very rich and diverse clade includes several clearly separable species-groups the relegation of which has been frequently changed during the last decades. Actually, the lumping trend dominates and the major lineages are all amalgamated into the common and giant genus Xestia Hübner, 1818 counting more than 300 species, which are placed in a number of subgenera. One of these subgenera is Pachnobia Guenée, 1852 which comprises, besides others, the species formerly placed into the genera/subgenera Pachnobia, Anomogyna Staudinger, Schoyenia Aurivillius, and Hyptioxesta Rebel.